Object Metamorphosis Based on Generalized Morphology Transformation - Li, Hua; Liu, Wenyu; Zhu, Guangxi; Zhu, Yaoting (International Journal of Virtual Reality, 2001)
A metamorphosis or a morphing is the process of continuously transforming one object into another, and are popular in computer animation, industrial design, and growth simulation. In this paper, a novel approach is presented for computing continuous shape transformation between polyhedral objects in this paper. Metamorphosis can be achieved by decomposing two objects into sets of individual convex sub-objects respectively and constructing the mapping between two sets, this method can solve the metamorphosis problem of two non-homotopic objects (including concave objects and holey objects). The results of object metamorphosis are discussed in this paper. The experiments show that this method can generate natural, high quality metamorphosis results with simple computation. This method can also be used in font composition and interpolation between two keyframes in 2D and 3D computer animation automatically.